Does the Bijak Wang (Smart Money) programme benefit schoolgoing children? - Sabri, Mohamad Fazli; Moga Dass, Thinagaran; Lee, May Poh; Zakaria, Normadia Liz; Wahab, Rozita; Ramli, Nurhayatul Nira (Malaysian Consumer and Family Economics Association, 2017)
The Bijak Wang or Smart Money programme is a half-day interactive workshop on money and money management targeted at children aged 10 to 12 years. The objective of the programme is to develop financial literacy through the use of an interactive games kit i.e. Smart Money Kit: Bright Kids Smart Money. This innovative programme was developed as an alternative learning and teaching tool for children to acquire personal financial management knowledge and skills with guidance from parents and adults. The kit comprises conservative board games that help to sharpen children’s soft skills in communication, strategic planning and critical thinking. Research literature has revealed that instilling money management knowledge and skills in children will impact positively on them, empowering them to manage better their finances in future. The concept behind this programme is learning through play. This programme was conducted with four groups of participants from different geographical areas. Participants engaged in gameplay with Profesor Bijak Wang and Ekspedisi ABCD which are both board games; Cuba Ingat dan Teka which is a flash card game; and Reka Tabung ABCD. All these games are highly integrated with the six basic money management concepts. As the participants play, they undergo cognitive absorption of money management concepts, which they will tend to apply in their future daily lives. Pre and post-testing using a self-administrated questionnaire was conducted to analyse the level of money management skills and knowledge the children had before participating in the programme and the level that they had acquired after they had participated in the various gameplays. The results of the post-test show that the children’s financial literacy improved with their increased acquisition of money management skills and knowledge as compared to the level they initially had as revealed by the results of the pre-test conducted. This indicates that children learn effectively through interactive learning using the Smart Money Kit: Bright Kids Smart Money. As such, parents and teachers should use innovative and creative approaches in educating children about money and money management and treat this learning as a lifelong process so children will make prudent financial decisions in their future.